Pengaruh Penggunaan Model Pembelajaran Berbasis Masalah terhadap Hasil Belajar Siswa - Al Ikhlas; Junita Intan Pradana; L. Fatimatuz Zahro; Rika Anggereini; Gema Takbir Al Akbar (Departement of Mathematics Education, 2023)
This study aims to determine the effect of problem-based learning models on students' achievement. This research was conducted by pseudo-experimental research methods. The study population is students of SMP Country 36 Kerinci Class VIII Semeseter even for the 2022/2023 academic year. The research sample consisted of an experimental class of 32 students and a control class of 31 students. Data collection is carried out using instruments, namely student learning outcome test instruments in the form of essays. The results of data analysis and statistical tests show that problem-based learning models affect student learning outcomes. Based on the results of processing research data or by hypothesis testing so that a conclusion can be drawn about the effect of learning model factors on learning outcomes it can be seen that fcalculate = 12.879 with the value Sig. 0.000. Because the value of Sig. < 0.05, Ho is rejected, or in other words there is an influence of problem-based learning models on students' achievement. Based on the results of the study, it is recommended to teachers, that the application of problem-based learning models be developed as an innovation in the teaching and learning process to create an active, innovative, creative, effective and fun learning and able to improve students' achievement